2008
DOI: 10.1101/gad.487508
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Escherichia coli sister chromosome cohesion by topoisomerase IV

Abstract: A body of evidence supports the idea that newly replicated Escherichia coli chromosomes segregate progressively as replication progresses, with spatial separation of sister genetic loci occurring ∼15 min after their replication. We show that the time of this cohesion can be modulated by topoisomerase IV (TopoIV) activity. Impairment of TopoIV prevents segregation of newly replicated sister loci and bulk chromosome segregation, whereas modest increases in TopoIV decrease the cohesion time substantially. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
157
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(177 citation statements)
references
References 27 publications
15
157
1
4
Order By: Relevance
“…An image was taken every 10 min. lication initiation occurs efficiently under these conditions, most of the newly replicated loci have not segregated (47,59). By 70 min after replication initiation, the rifampin-treated and rifampin-free cultures showed essentially identical distributions of foci, with Ͼ80% of the cells containing two or more ori1 foci.…”
Section: Vol 192 2010 E Coli Origin Segregation 6147mentioning
confidence: 94%
“…An image was taken every 10 min. lication initiation occurs efficiently under these conditions, most of the newly replicated loci have not segregated (47,59). By 70 min after replication initiation, the rifampin-treated and rifampin-free cultures showed essentially identical distributions of foci, with Ͼ80% of the cells containing two or more ori1 foci.…”
Section: Vol 192 2010 E Coli Origin Segregation 6147mentioning
confidence: 94%
“…Progress in understanding the structure/function mechanics of the bacterial chromosome greatly improved with development of techniques that allow real time visualization of bacterial nucleoids inside living cells and the ability to follow specific chromosomal loci using fluorescent labels (Kleckner et al 2014;Wang et al 2008). Nucleoids are self-adherent filaments stochastically organized locally into approximately 10-kb domains in growing cells (Cunha et al 2005;Espeli et al 2008;Hadizadeh Yazdi et al 2012;Postow et al 2004;Stein et al 2005;Wiggins et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is direct evidence that some fork rotation does take place during elongation in E. coli and indirect evidence that fork rotation occurs during elongation in eukaryotic systems. In E. coli, cytological marking of DNA loci with fluorescent proteins has shown that a number of newly replicated loci appear "cohesed" for a short period following replication [36]. The time of cohesion following replication is directly related to topo IV dosage, with decreased dosage increasing the time of cohesion and increased dosage reducing it [36], arguing that the cohesion was maintained by DNA catenations formed by fork rotation and resolved by topo IV action.…”
Section: Frequency Of Fork Rotation and Catenane Formation By Elongatmentioning
confidence: 99%
“…In E. coli, cytological marking of DNA loci with fluorescent proteins has shown that a number of newly replicated loci appear "cohesed" for a short period following replication [36]. The time of cohesion following replication is directly related to topo IV dosage, with decreased dosage increasing the time of cohesion and increased dosage reducing it [36], arguing that the cohesion was maintained by DNA catenations formed by fork rotation and resolved by topo IV action. Therefore it seems reasonable to assume that a small amount of fork rotation and DNA catenation occurs during elongation to maintain transient cohesion behind the fork.…”
Section: Frequency Of Fork Rotation and Catenane Formation By Elongatmentioning
confidence: 99%
See 1 more Smart Citation